Geneza i rozwój systemu franchisingu w USA (na przykładzie sieci McDonald's) i jego ekspansja w Europie - Mróz, Barbara; Hryniewiecki, Rafał (The Genesis and Evolution of Franchising System in the USA (on the Example of McDonald's net) and the Expansion in Europe, 2008)
The term "franchising" comes from feudal France. Today it is used to describe a sales system, where a right to use a particular trade mark is given to the sales of goods and supply of services. Franchising gives a chance, to a small and medium sized companies, to achieve a meaningful position at the market. The word "success" describes most of the franchising networks, hence, companies like McDonald's need neither to be introduced, nor advertized.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 158-164